Knowledge About Hypertensive Kidney Disease Among Adults: A Cross-sectional Study - Bhowmik, Mustary; Dhar, Soumyodipi; Sikder, Saikat (STIKes Al-Ma'arif Baturaja, 2025)
Hypertensive kidney disease represents a growing public health concern, particularly in urban populations with high hypertension prevalence. Despite its preventable nature, limited awareness about this complication persists, contributing to delayed diagnosis and poor outcomes. This study aimed to assess knowledge levels about hypertensive kidney disease among adults in urban areas and identify associated demographic and health factors. A cross-sectional study was conducted with 95 participants aged 20-65 years, selected through convenience sampling. Knowledge was assessed using a structured questionnaire and categorized into good (≥70% correct answers), moderate (50-69%), and poor (<50%) levels. Data analysis examined associations between knowledge levels and demographic characteristics. The study revealed concerning knowledge gaps: only 32.6% of participants demonstrated good knowledge, while 45.3% had moderate understanding, and 22.1% showed poor knowledge. Significant associations were found between knowledge levels and education (p<0.01), hypertension history (p<0.05), and age (p<0.05). Participants with higher education and personal/family history of hypertension showed better knowledge. Younger adults (20-39 years) had significantly poorer understanding compared to older age groups. Substantial knowledge deficiencies exist regarding hypertensive kidney disease, particularly among younger individuals and those with lower education. These gaps highlight the urgent need for targeted educational interventions.